Assessment of New Economic Reforms In Banking Industry: Examining the Impact of Banking Reforms in India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Emerging markets anddeveloping economies face one of the central issues namely strengthening offinancial systems. This is due to the reason that sound financial systems serveas an important channel for the achievement of economic growth through themobilization of financial savings, putting them to productive use andtransferring various risks. Many countries adopted a series of financial sectorliberalization measures in the late 1980s and early 1990s that includedinterest rate liberalization, entry deregulations, reduction of reserverequirements and removal of credit allocation. In many cases, the timing offinancial sector liberalization coincided with that of capital accountliberalization. Domestic banks were given access to cheap loans from abroad andallocated those resources to domestic production sectors. Since the Asianfinancial crisis of 1997-1999, the importance of balancing financial liberalizationwith adequate regulation and supervision prior to full capital accountliberalization has been increasingly recognized. The crisis was preceded bymassive, unhedged short –term capital inflows, which then aggravated doublemismatches and undermined the soundness of the domestic financial sector. Amaturity mismatch is generally inherent in the banking sector since commercialbanks accept short-term deposits and convert them into relatively longer-term,often illiquid, assets. Nevertheless, massive, predominantly short-term capitalinflows-largely in the form of inter-bank loans-shortened banks’ liabilitiesthus expanding the maturity mismatch. This paper focuses on India’s bankingsector, which has been attracting increasing attention since 1991 whenfinancial reform programme was launched. This paper throws light on some of thedevelopments that have taken place in the Indian banking sector and challengesahead for the banking sector as a result of process of banking reformsinitiated in 1992.